2021
DOI: 10.1080/21655979.2021.2012628
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The long non-coding RNA ASMTL-AS1 promotes hepatocellular carcinoma progression by sponging miR-1343-3p that suppresses LAMC1 (laminin subunit gamma 1)

Abstract: Long non-coding RNAs (lncRNAs) are critical regulators of hepatocellular carcinoma (HCC) carcinogenesis and development. We aimed to identify the function of the lncRNA ASMTL-AS1 during HCC malignancy. The expression of ASMTL-AS1, miR-1343-3p, and LAMC1 (laminin subunit gamma 1) was assessed in HCC tissues and cells. Cell Counting Kit-8 (CCK8) and Transwell migration assays were performed to determine the effect of ASMTL-AS1 on HCC cell proliferation and migration. Cell apoptosis was identified by detecting Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recent studies have found that LINC01559 promotes lung cancer cell proliferation and migration in vitro by enhancing the autophagy signaling pathway via sponging hsa-miR-1343-3p [ 29 ]. In HCC, the lncRNA ASMTL-AS1 acts as a carcinogen, competing with hsa-miR-1343-3p that suppressing LAMC1 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that LINC01559 promotes lung cancer cell proliferation and migration in vitro by enhancing the autophagy signaling pathway via sponging hsa-miR-1343-3p [ 29 ]. In HCC, the lncRNA ASMTL-AS1 acts as a carcinogen, competing with hsa-miR-1343-3p that suppressing LAMC1 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because ASMTL-AS1 and miR-1270 were negatively correlated in expression level, miR-1270 mimic can reduce the fluorescence intensity of the wide-type ASMTL-AS1, and ASMTL-AS1 could pull down miR-1270. The ceRNA role of ASMTL-AS1 was also found in osteosarcoma with miR-342-3p, hepatocellular carcinoma with miR-1343-3p, and breast cancer by sponging miR-1228-3p [ 12 , 13 , 31 , 32 ]. Given the dysregulation of ASMTL-AS1 and miR-1270 in gastric cancer, whether ASMTL-AS1/miR-1270 regulatory loop affects the cell biological behaviors of gastric cells was further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-26a-5p can alleviate cardiac hypertrophy and dysfunction ( Shi et al, 2021 ) and protect against myocardial ischemia/reperfusion injury ( Xing et al, 2020 ). Mir-1343-3p plays a significant role in the development of human cancers such as lung cancer ( Zhang et al, 2020 ), colorectal carcinoma ( Bhat et al, 2022 ), and hepatocellular carcinoma ( Mou and Sun, 2022 ). The involvement of mir-1343-3p in cardiovascular diseases is also reported ( Sharma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%